ChemInform Abstract: A Sequential Pd/Norbornene‐Catalyzed Process Generates o‐Biaryl Carbaldehydes or Ketones via a Redox Reaction or 6H‐Dibenzopyrans by C—O Ring Closure. Issue 14 (20th March 2013) - Motti, Elena; Della Ca, Nicola; Xu, Di; Piersimoni, Anna; Bedogni, Elena; Zhou, Zhi‐Ming; Catellani, Marta
Abstract An excess of norbornene has to be used, the molar ratio of norbornene to Pd varies between 5:1 to 20:1.